Thickness dependence on the optoelectronic properties of multilayered GaSe based photodetector. (29th June 2016) - Ko, Pil Ju; Abderrahmane, Abdelkader; Takamura, Tsukasa; Kim, Nam-Hoon; Sandhu, Adarsh
Abstract: Two-dimensional (2D) layered materials exhibit unique optoelectronic properties at atomic thicknesses. In this paper, we fabricated metal–semiconductor–metal based photodetectors using layered gallium selenide (GaSe) with different thicknesses. The electrical and optoelectronic properties of the photodetectors were studied, and these devices showed good electrical characteristics down to GaSe flake thicknesses of 30 nm. A photograting effect was observed in the absence of a gate voltage, thereby implying a relatively high photoresponsivity. Higher values of the photoresponsivity occurred for thicker layers of GaSe with a maximum value 0.57 AW −1 and external quantum efficiency of of 132.8%, and decreased with decreasing GaSe flake thickness. The detectivity was 4.05 × 10 10 cm Hz 1/2 W −1 at 532 nm laser wavelength, underscoring that GaSe is a promising p-type 2D material for photodetection applications in the visible spectrum.